HARMONI DALAM BERDAKWAH: RELEVANSI HADIS KELEMAHLEMBUTAN DALAM MERESPONS KONTROVERSI TOKOH PUBLIK DI ERA MODERN - Zakka, Fathoniz Zakka; Yulia Ferdadian Vikarino (Bahasa Indonesia, 2026)
The digital age has transformed social media into a vast public forum. While promoting free expression, it often devolves into cyberbullying and public shaming against government figures, including President Prabowo Subianto's administration and the House of Representatives. Sociologically and psychologically, this confrontational approach is ineffective; rather than encouraging constructive policy changes, it triggers defensiveness in leaders and deepens social polarization. Using a qualitative library research method, this study examines the Islamic concept of gentleness (rifq) and the specific guidance in Hadith Musnad Ahmad No. 15333 on communicating with leaders. By applying descriptive-analytical methods, the research bridges prophetic wisdom with contemporary political communication. The findings reveal that prophetic traditions strongly recommend advising leaders privately to preserve their dignity, which lowers their defenses and encourages genuine self-reflection. Consequently, this study introduces "Harmony in Preaching” a communication model rooted in a "Religion with Love" approach. It adapts classical private advice for the modern era by suggesting dignified alternatives like formal institutional dialogues, closed-door meetings, and polite digital engagement focused purely on policy substance. Ultimately, this elegant strategy ensures that Indonesia's vibrant democracy can thrive alongside Islamic ethical values.